OUTCOME OF EXTRA-MUCOSAL SMALL GUT ANASTOMOSIS IN A PERIPHERAL HOSPITAL - Hussain, Dildar; Sarfaraz, Khurram (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the outcome of extra-mucosal small gut anastomosis (interrupted) in terms of hospital stay, mortality and anastomosis-related complications. Material and Methods: This was a hospital based, prospective and descriptive study, conducted in the General Surgical Ward of Agency Headquarter Hospital, Parachinar, Pakistan from 1st December 2005 to 31st November 2006. A total of hundred consecutive cases of extra mucosal small gut anastomosis, admitted through casualty or OPD were included in the study. Special proformas were designed for each patient from the date of admission till discharge from the hospital and for follow up upto three months. Patients with intestinal perforations due to fire arm injuries, stab wounds, ileostomy closures, stricturoplasties were included in the study. Patients with diabetes mellitus, malignancies, children under 12 years of age and patients with associated multi organ injuries (liver, spleen, colon etc) were excluded from the study. Results: Mean hospital stay was 9.4 (± 3 S.D.) days. Male to female ratio was 2.9:1. Mortality rate was 1%.Wound dehiscence and abscess formation were the main complications (8% each) followed by peritonitis (6%) secondary to anastomotic dehiscence. Conclusion: Single layer extra mucosal small gut interrupted anastomosis with vicryl 2/0 was found to be an acceptable procedure regarding hospital stay, mortality and anastomosis related complications.